Proposal for an in vivo histopathologic scoring system for skin aging by means of confocal microscopy. Issue 1 (7th June 2012) - Longo, Caterina; Casari, Alice; De, Barbara; Simonazzi, Silvia; Mazzaglia, Giovanna; Pellacani, Giovanni
<x xml:space="preserve">Abstract</x> Background Many instrumental devices have been testing in analysing and quantifying the skin aging signs. However, histopathology still remains the only methods that allow a microscopic assessment of the skin. However, a skin biopsy is not feasible in aesthetically critical areas such as the face. Recently, confocal microscopy has been discovered as a noninvasive tool with a nearly histologic resolution. Distinct morphologic confocal aspects on facial skin have been described and correlated with the histopathologic counterparts. Objectives In our study we aim to develop an easy to use confocal aging score to quantify the skin aging related signs. Methods A sample of facial skin of fifty volunteers has been subjected to confocal imaging. Combining the previously identified confocal features, three different semi‐quantitative scores were calculated: – epidermal disarray score (irregular honeycombed pattern + epidermal thickness + furrow pattern); – epidermal hyperplasia score (mottled pigmentation + extent of polycyclic papillary + epidermal thickness; – collagen score (curled fibers, 2 for huddles of collagen, 1 for coarse collagen structures, and 0 for thin reticulated collagen) Results The epidermal disarray score showed a stable trend up to 65 years and a dramatic increase in the elderly subjects epidermal. Hyperplasia score was characterized by an ascending trend from younger subjects to middle age. The total collagen score showed a progressive trend with age with a different proportion of distinct collagen type. Conclusions RCM is a powerful, noninvasive technique that could permit to microscopically quantify the aging signs and to test cosmetic efficacy.